The perceived entrepreneurial characteristics of Malaysian Living Skill teachers: implication for teacher preparation programme - Bakar, Ab. Rahim; Lope Pihie, Zaidatol Akmaliah; Konting, Mohd Majid; Angking, Genevieve Klang (Universiti Putra Malaysia Press, 2001)
Entrepreneurial efforts in the form of small, new businesses have become an important force in the economic growth of a nation. Living Skills subject (KHB) with an entrepreneurship component was introduced in the Malaysian school curriculum since 1988, but a question arise whether the teachers themselves possess the entrepreneurial characteristics needed. A survey was conducted to investigate the levels of the perceived entrepreneurial characteristics of the Integrated Living Skills teachers (KHB) in Malaysian secondary schools. Findings indicated that a majority of the teachers participated in the study had a moderate level of perceived entrepreneurial characteristics. Male teachers were more entrepreneurial compared to female teachers. The entrepreneurial characteristics of teachers ,with different teaching responsibility did not differ. Teachers who aspired for entrepreneurship were more entrepreneurial than the teachers who did not have such an aspiration. It is believed that all KHB teachers should possess the entrepreneurship characteristics and it can be developed through in-service training. It is suggested that all teacher education programme should have a 3 credit course in entrepreneurship education.